The Oxford Olympics study 2016: Cost and cost overrun at the games - Flyvbjerg, B.; Budzier, A.; Stewart, A. (University of Oxford, 2016)
Given that Olympic Games held over the past decade each have cost USD 8.9 billion on average, the size and financial risks of the Games warrant study. The objectives of the Oxford Olympics study are to establish the actual outturn costs of previous Olympic Games in a manner where cost can consistently be compared across Games; establish cost overruns for previous Games, i.e., the degree to which final outturn costs reflect projected budgets at the bid stage, again in a way that allows comparison across Games; test whether the Olympic Games Knowledge Management Program has reduced cost risk for the Games, and, finally, benchmark cost and cost overrun for the Rio 2016 Olympics against previous Games. The main contribution of the Oxford study is to establish a phenomenology of cost and cost overrun at the Olympics, which allows consistent and systematic comparison across Games. This has not been done before. Main findings of the study are, first, that average actual outturn cost for Summer Games is USD 5.2 billion (2015 level), and USD 3.1 billion for Winter Games. The most costly Summer Games to date are London 2012 at USD 15 billion; the most costly Winter Games Sochi 2014 at USD 21.9 billion. The numbers cover the period 1960-2016 and include only sports-related costs, i.e., wider capital costs for general infrastructure, which are often larger than sports-related costs, have been excluded. Second, at 156 percent in real terms, the Olympics have the highest average cost overrun of any type of megaproject. Moreover, cost overrun is found in all Games, without exception; for no other type of megaproject is this the case. 47 percent of Games have cost overruns above 100 percent. The largest cost overrun for Summer Games was found for Montreal 1976 at 720 percent, followed by Barcelona 1992 at 266 percent. For Winter Games the largest cost overrun was 324 percent for Lake Placid 1980, followed by Sochi 2014 at 289 percent. Third, the Olympic Games Knowledge Management Program appears to be successful in reducing cost risk for the Games. The difference in cost overrun before (166 percent) and after (51 percent) the program began is statistically significant. Fourth, and finally, the Rio 2016 Games, at a cost of USD 4.6 billion, appear to be on track to reverse the high expenditures of London 2012 and Sochi 2014 and deliver a Summer Games at the median cost for such Games. The cost overrun for Rio - at 51 percent in real terms, or USD 1.6 billion - is the same as the median cost overrun for other Games since 1999. Given the above results, for a city and nation to decide to stage the Olympic Games is to decide to take on one of the most costly and financially most risky type of megaproject that exists, something that many cities and nations have learned to their peril.